1995
DOI: 10.1103/physrevb.52.2395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hole doping on the electronic structure ofNd1xSr

Abstract: Photoelectron spectroscopy has been employed to follow the development of the electronic structure in Nd, "Sr"TiO3 as a function of x. Resonant effects at the Ti 3p threshold were used to highlight Ti 3d contributions in the valence bands. Particular attention is focused on Ti 3d intensity within -3 eV of the Fermi level (Ez). The total intensity in this region is found to correlate linearly with composition, as expected. Changes in the shape of this spectral structure are discussed in terms of the one-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
3
15
2
Order By: Relevance
“…From an analysis of optical-conductivity spectra [5,6] and transport and magnetic measurements [7] of Sr 1Àx La x TiO 3 (0 6 x 6 1), it was concluded that this system behaves as a Fermi liquid for small doping (x < 0:5). Even for very small x (down to x ¼ 0:1), however, this conclusion contradicts most previous photoemission results on metallic Sr 1Àx R x TiO 3 (R ¼ La [8,9] and Nd [10,11]) and metallic Ba 1Àx R x TiO 3Àd (R ¼ Y, La, and Nd [12,13]). It was shown that a prominent state induced by doping electron carriers appears at the binding energy of about 1.5 eV below the Fermi level (E F ), which cannot be explained by a simple picture of d-band filling or by the Fermi liquid behavior as suggested by the optical spectra.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…From an analysis of optical-conductivity spectra [5,6] and transport and magnetic measurements [7] of Sr 1Àx La x TiO 3 (0 6 x 6 1), it was concluded that this system behaves as a Fermi liquid for small doping (x < 0:5). Even for very small x (down to x ¼ 0:1), however, this conclusion contradicts most previous photoemission results on metallic Sr 1Àx R x TiO 3 (R ¼ La [8,9] and Nd [10,11]) and metallic Ba 1Àx R x TiO 3Àd (R ¼ Y, La, and Nd [12,13]). It was shown that a prominent state induced by doping electron carriers appears at the binding energy of about 1.5 eV below the Fermi level (E F ), which cannot be explained by a simple picture of d-band filling or by the Fermi liquid behavior as suggested by the optical spectra.…”
Section: Introductioncontrasting
confidence: 75%
“…From a comparison between the UPS spectra for the fractured surface and those for the scraped surface, it was shown that the spectral intensity of the metallic state is considerably suppressed by scraping the surface. Because of the extreme sensitivity to the surface preparations, most previous photoemission studies on the scraped surfaces have not shown the metallic state clearly [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we adopt a local description of the electronic structure: the coherent states and IGSs originate from Ti sites initially having nominally-d 1 configuration (the same initial state to that of the Ti 3+ peak in the Ti 2p 3/2 spectrum). This interpretation is supported by the observation [8,14] that the spectral weight of the region including the coherent states and the IGSs scales with x, which is similar to the Ti 3+ -component weight in the Ti 2p 3/2 spectra scaling with x [15]. Then, the mixed character of p and d in the IGSs can be explained as the final state composed of d 1 L (L denotes a hole in the O 2p ligand orbital) and d 0 , since the former has p character while the latter has d character.…”
supporting
confidence: 70%
“…The Ti 2p 3/2 spectrum of STO:Nb showed a weak Ti 3+ peak at ∼2 eV below the main Ti 4+ peak at E B = 459.5 eV. From the intensity ratio of Ti 3+ /Ti 4+ peaks [14,15], we deduced x = 0.06±0.02. This value was consistent with x < 0.1 estimated from the Ti 2p XAS line-shape broadening [ Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation